Criteria for Decent Social Security: Theory, Legislation, and Law Enforcement Practice - M. Yu. Fedorova (Сибирское юридическое обозрение, 2025)
This article examines the constitutional foundations of social security, relevant provisions of Russian legislation, and their practical application, taking into account the constitutional amendments of 2020. The objective is to define the concept of decent social security and to develop a system of criteria for its evaluation. The study employs a systematic, historical-legal, and formal-legal methodology. The starting point for establishing criteria is the constitutional principle of the welfare state, which has been interpreted by the Constitutional Court in connection with various forms of social benefits. The constitutional right to social security is closely intertwined with the right to human dignity. Accordingly, social security may be considered “decent” if it provides individuals with payments and services that uphold their dignity, help maintain their health, support a socially active lifestyle, and ensure the exercise of their right to benefits under legally established terms and through effective administrative procedures. To assess whether social security meets the threshold of decency, a system of criteria must be developed, grounded in the specific nature of the right to social security and the legal and organizational mechanisms of its implementation. The scope and content of the subjective right to social security form its direct (immediate) criteria. Indirect (structural and institutional) criteria assess the efficiency of the national social security system in terms of its comprehensiveness in mitigating social risks. The principal direct criterion is the socially acceptable level of social security. In Russia, this is currently expressed through the concept of the subsistence minimum, which has an economic dimension and reflects the lowest acceptable level of basic needs satisfaction. For certain categories of beneficiaries, the economic criterion is further supplemented by legal considerations – such as special needs, legal status, or the specific conditions for acquiring entitlements within the mandatory social insurance system. In addition, decent social security is subject to legal criteria, which play an important role in determining, for example, compensation for moral harm in disputes arising from social security relationships – particularly where citizens’ rights to receive benefits and services are exercised in accordance with the law and proper procedures.